Exploring barriers and drivers to a modified WHO safe childbirth checklist implementation in three West African countries: a qualitative study using the updated consolidated framework for implementation research - Kadidiatou Raïssa Kourouma; Kadidiatou Raïssa Kourouma; Wambi Maurice Evariste Yaméogo; Wambi Maurice Evariste Yaméogo; Daouda Doukouré; Daouda Doukouré; Alpha Oumar Sall; Marie Laurette Agbré Yacé; Marie Laurette Agbré Yacé; Tiéba Millogo; Tiéba Millogo; Mamadou Diouldé Baldé; et al. (Frontiers in Health Services)
IntroductionSub-Saharan Africa faces the highest maternal and newborn mortality and morbidity rates globally. The World Health Organization Safe Childbirth Checklist (WHO SCC) was developed to address this issue by promoting evidence-based practices during childbirth. This study explored the barriers and drivers to implementing a modified WHO SCC (mSCC) in Burkina Faso, Cote d'Ivoire, and Guinea.MethodsA qualitative multiple case study design was conducted from May to June 2023, involving individual interviews with diverse stakeholders (n = 110) across four regional hospitals in each country. The mSCC was implemented in these hospitals along with training and coaching. Data was analyzed using thematic analysis, guided by the updated CFIR framework. Nvivo 14 was used for coding.ResultsThe study identified 17 drivers and 7 barriers. Key drivers included the mSCC's clarity, simplicity and alignment with national guidelines, training, coaching, and stakeholders’ engagement. in these 3 countries. Barriers were mainly related to resource constraints (medicines, supplies, staffing, and space), increased workload, and lack of incentives. Specific barriers for Burkina Faso and Cote d’Ivoire were the lack of incentives and the positioning of the Kakemono in confined space only in Cote d'Ivoire. Despite these challenges, the mSCC was generally well-received, with strong support from leadership and implementation facilitators contributing to its integration into routine care.ConclusionThis study highlighted the importance of addressing resource limitations, optimizing workload, and providing incentives to ensure successful mSCC implementation. Findings underscored the need for context-specific strategies and strong leadership support when introducing similar interventions in resource-constrained settings.